Application of the Principle of Lex Specialis Derogat Legi Generali in the Settlement of Cybersquatting Domain Name Disputes at the National Arbitration Institution - Richard Herlambang; Megawati Barthos (Greenation Research & Yayasan Global Resarch National, 2025)
The development of information technology has increased the strategic value of domain names as digital identities and intellectual property assets. However, in practice, the phenomenon of cybersquatting has emerged, namely the registration of domain names by unauthorized parties to control or profit from similarities with well-known trademarks. This phenomenon has given rise to legal conflicts between brand owners and domain name holders, while national regulations have not explicitly regulated the dispute resolution mechanism. This article aims to analyze the application of the principle of lex specialis derogat legi generali in resolving cybersquatting disputes through national arbitration institutions, specifically the Indonesian Internet Domain Name Manager (PANDI). This research uses a normative juridical method with a statutory approach and literature study. The results of the discussion indicate that Law No. 20 of 2016 concerning Trademarks and Geographical Indications should be positioned as lex specialis compared to Law No. 11 of 2008 in conjunction with Law No. 19 of 2016 concerning Information and Electronic Transactions (ITE), considering that the object of the dispute is closely related to the protection of intellectual property rights. Furthermore, PANDI's domain arbitration rulings have not yet received full legal recognition in the national judicial system, thus reducing the effectiveness of their resolution. The establishment of specific regulations governing domain names and their dispute resolution is necessary to provide legal certainty and comprehensive protection for brand owners in the digital realm